Correlation between somatic heteromorphism and the germinative response of seeds of Mastichodendron foetidissimum (Jacq.) Cronq. - Sanchez, Jorge A.; Muñoz, Barbara; Orta, Ramon; Calvo, Eric; Herrera, Ricardo (Instituto de Ecología, A.C., 1997)
Mastichodendron foetidissimum (Jacq.) Cronq. is a tree characterized by heteromorphic seeds, which differ greatly in shape and size as a result of their number (1, 2 or 3) in each fruit. In this paper the correlation between this variability and the germinative response of the seeds was determined. The seeds were classified into three categories, according to their shape (morphs I, II and III), corresponding to the number of seeds per fruit. For each morph, length, width, thickness, fresh weight, dry weight, content of humidity and percent of germination were determined. All the parameters differ between morphs, except the humidity content. The morphological variability shows a clear correlation with the germinative response: the heavier seeds (morph I) display the larger percentages of germination.